(3GdYhOI ef GdeOQSI ecGfI GdCHhjf aj GdJYde GdeOQSjs - (3Hjdjajh, eGQj cdhOs ((3HjQhJs (3OGQ Gdbdes, 2007)
(3GdgOa ef gPG GdcJGH JbOje hSGFd ddhGdOjf JecfgeG ef GdGfNQGW HfTGW aj MjGI GdWad GdeOQSjI(B. (3hYdi GdNUhU Vef aYGdjGJ CNQi, GdJONd aj dMXGJ GdhGLHGJ GdeOQSjI hJMVjQ GdOQhS, eY JTLjY GSJbdGdg hhUhdg Edi GdMS HGdeSDhdjI(B. (3afaYd (B"(3HUhQI CNQi(B" (3YhVkG Yf Cf faYd (B"(3CcKQ(B". (3hgj UhQI CNQi dEOQGc GdOhQ GdPj jecf Cf jbhe Hg GdhGdOGf(B. (3hYfOeG jJeKdGf eG JbOeg GdeOQSI ef GdJYdje, hWQjbI EOQGLgG deMJhjGJg aj GdMjGI GdjhejI, HCSQY UhQI ahQjI eecfI, jSJWjYGf eSGYOI WadgeG Ydi Cf jLO ajgG eYfi haGFOI, Hd hGdeJYI CjVkG(B. (3haj GdbSe GdChd ef gPG GdcJGH Je efGbTI eTcdI GdefGN GdYGWaj GdPj jJhLH Ydi GdhGdOjf eMGhdI EbGeJg Mhd GdMjGI GdeOQSjI dWadgeG, heSGYOJg Ydi GdGfNQGW HUhQI fTjWI aj GdeOQSI(B. (3hJeJ eYGdLI JOQL GdJYdje hGdeTGQcI GdJj jecf Cf jMedgG GdCHhGf ddJMSjf hGdOYe, hHGdJGdj deSGYOI GdWad Ydi GdJYde(B.(3haj GdbSe GdKGfj Je YQV HYV GdhSGFd GdedehSI GdJj JSGYO GdCHhjf Ydi JWHjb GdeHGOF GdCSGS GdeYdfI aj GdbSe GdChd, hgj hSGFd JSGYO GdCHhjf Ydi JfejI ehGba hGSJQGJjLjGJ HgOa GdJYde(B, (3hJLYd GdWad bGOQkG Ydi EJbGf egGQGJ heYGQa HGdbOQ faSg Vef hGLHGJg haj OQhSg, hNdGd fTGWGJg GdjhejI(B. (3hdG HO ef GdETGQI CNjQkG Edi Cf GdhSGFd GdebJQMI aj GdbSe GdChd ef gPG GdcJGH JJhLg eHGTQI Edi GdCHhjf, HjfeG JNJU Jdc GdebJQMI aj GdbSe GdKGfj HGdWad faSg(B.s
(3GdfhY (B: (3cJGHs
Keywords: Etablissement scolaire et parents; School and Parents; (3GdeOQSI hGdCgds